2021
DOI: 10.1021/acs.jpcb.1c07508
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric Investigation of Hydrogen-Atom Sublattice Transitions in the Ice VI/XV/XIX Trio

Abstract: Ice XIX represents the latest discovery of ice polymorphs and exists in the medium pressure range near 1–2 GPa. Ice XIX is a partially hydrogen-ordered phase, by contrast to its disordered mother phase ice VI, which shares the same oxygen-atom network with ice XIX. Ice XIX differs in terms of the ordering of the hydrogen-atom sublattice, and hence the space group, from its hydrogen-ordered sibling ice XV, which also features the same type of oxygen network. Together, ice VI, XV, and XIX form the only known tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…28 According to Gasser's report, ice XIX is a ''partially hydrogen-ordered'' phase. 4,20 Yamane et al also reported that the unit cell of ice XIX allows many possible hydrogen-ordered configurations. 21 Since the totally hydrogen disordered structure is ice VI, we proposed that the real structure of ice XIX maybe a big supercell cell contains many hydrogen ordered…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 According to Gasser's report, ice XIX is a ''partially hydrogen-ordered'' phase. 4,20 Yamane et al also reported that the unit cell of ice XIX allows many possible hydrogen-ordered configurations. 21 Since the totally hydrogen disordered structure is ice VI, we proposed that the real structure of ice XIX maybe a big supercell cell contains many hydrogen ordered…”
Section: Resultsmentioning
confidence: 99%
“…3,4 Gasser et al revealed the transformation relationship between ice VI, ice XV and ice XIX based on calorimetry experiments. 20 Yamane et al believed that ice XIX exists at higher pressure, and because the density of ice XIX is greater than that of ices XV and VI, ice XIX is more stable. 21 As mentioned, ice XIX is hydrogen-ordered phase and has the same oxygen sublattice structure as ices VI and XV; the structures of ices XIX and XV differ in the positions of their hydrogen atoms and in their space groups.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the oxygen topology was found to be the same in ice VI, XV (Salzmann et al, 2009) and XIX (Gasser et al, 2021a(Gasser et al, , 2018Yamane et al, 2021;Salzmann et al, 2021). While disordered phase VI, ordered phase XV and partially ordered phase XIX form a kind of family of ice structures where transitions from ordered to ordered, ordered to disordered, and disordered to ordered are possible (Gasser et al, 2021b). Structural distortions are claimed to be the main structural feature of ice XIX (Salzmann et al, 2021).…”
Section: Introductionmentioning
confidence: 91%
“…These two scenarios need to be distinguished to understand disordered nature as seen in the arguments for ice XIX between the deep-glassy state Rosu-Finsen et al, 2020) and the new hydrogen-ordered phase (Gasser et al, 2018;Thoeny et al, 2019;Gasser, Thoeny, Greussing et al, 2021). Another explanation involving structural distortion was also raised (Salzmann et al, 2021) and the controversy continues.…”
Section: Evaluation Of the Completely Ordered Configuration In Sc13mentioning
confidence: 99%